The Protective Effect of 3-Deoxysappanchalcone on In Vitro Influenza Virus-induced Apoptosis and Inflammation - Yang, Fan; Zhou, Wei-Ling; Liu, Ai-Lin; Qin, Hai-Lin; Lee, Simon Ming-Yuen; Wang, Yi-Tao; Du, Guan-Hua (Planta Medica, 2012)
Influenza virus is one of the most important causes of acute respiratory disease. Viral infection and viral replication activate multiple cell signalling pathways. Apoptosis of infected cells and immune response against viral replication, which are generally considered to be protective mechanisms, are also probably mediated by viruses, which lead to severe health problems. We previously reported that 3-deoxysappanchalcone (3-DSC), a compound that is isolated from Caesalpinia sappan, exhibited in vitro anti-influenza activity. In the present study, we further identified that 3-DSC inhibited viral genomic replication and transcription only at a relatively high concentration. We then evaluated the effect of 3-DSC on the regulation of virus-induced cellular apoptosis. 3-DSC ameliorated virus-induced DNA fragmentation in a concentration-dependent manner, which tends to be a consequence of its inhibition of upstream caspase activation. 3-DSC also protected host cells against influenza-induced inflammation by suppressing CCL5 and CXCL10 secretions in endothelial cells and reducing the production of IL-6 and IL-1β in monocytes/macrophages. In conclusion, our results demonstrate that anti-influenza virus mechanisms of 3-DSC involved anti-apoptosis and anti-inflammation activities in vitro. Moreover, 3-DSC could be a promising drug candidate for influenza treatment.
Keywords: Caesalpinia sappan L.; Leguminosae; 3-deoxysappanchalcone; influenza; apoptosis; inflammation